Rock Glacier Characteristics Under Semiarid Climate Conditions in the Western Nyainqêntanglha Range, Tibetan Plateau - Buckel, Johannes; Reinosch, Eike; Voigtländer, Anne; Dietze, Michael; Bücker, Matthias; Krebs, Nora; Schroeckh, Ruben; Mäusbacher, Roland; Hördt, Andreas (Journal of Geophysical Research: Earth Surface, 2022)
Rock glaciers are receiving increased attention as a potential source of water and indicator of climate change in periglacial landscapes. They consist of an ice‐debris mixture, which creeps downslope. Although rock glaciers are a wide‐spread feature on the Tibetan Plateau, characteristics such as its ice fraction are unknown as a superficial debris layer inhibits remote assessments. We investigate one rock glacier in the semiarid western Nyainqêntanglha range (WNR) with a multi‐method approach, which combines geophysical, geological and geomorphological field investigations with remote sensing techniques. Long‐term kinematics of the rock glacier are detected by 4‐year InSAR time series analysis. The ice content and the active layer are examined by electrical resistivity tomography, ground penetrating radar, and environmental seismology. Short‐term activity (11‐days) is captured by a seismic network. Clast analysis shows a sorting of the rock glacier's debris. The rock glacier has three zones, which are defined by the following characteristics: (a) Two predominant lithology types are preserved separately in the superficial debris patterns, (b) heterogeneous kinematics and seismic activity, and (c) distinct ice fractions. Conceptually, the studied rock glacier is discussed as an endmember of the glacier—debris‐covered glacier—rock glacier continuum. This, in turn, can be linked to its location on the semiarid lee‐side of the mountain range against the Indian summer monsoon. Geologically preconditioned and glacially overprinted, the studied rock glacier is suggested to be a recurring example for similar rock glaciers in the WNR. This study highlights how geology, topography and climate influence rock glacier characteristics and development. Plain Language Summary: Climate change has begun to impact all regions of our planet. In cold regions, such as high‐mountain areas, rising temperatures lead to massive melting of glaciers. Besides this evident loss of ice, permafrost, a long‐term ice resource hidden in the ...